An algorithm for evaluating cylindricity according to the minimum condition. (1st July 2020) - Liu, Wenwen; Zhou, Xuhuai; Li, Hongli; Liu, Shanlin; Fu, Junsen
Highlights: The "minimax" evaluation model is transformed into a linear programming model. Solving and soft alignment are performed alternately to approximate the local minimum. Global-minimum cylindricity is searched by resetting the initial posture of the cylinder. Computer arbitration is implemented to verify whether a global minimum is reached. Abstract: Cylindricity evaluation plays an important role in processing quality evaluation. Accordingly, a new algorithm for evaluating cylindricity based on the minimum condition is presented. First, a theoretical "minimax" optimization model based on the minimum condition is linearized into a linear programming model. Then, the solution of the linear model and the soft alignment are performed alternately to approximate the local-minimum solution of the theoretical model. After the initial posture of the measured cylinder reset by the Monte Carlo method, the linear model is sequentially reconstructed and solved. The global-minimum solution of the theoretical model is determined by comparing the objective functions. Finally, computer arbitration for the minimum condition is conducted to determine whether the obtained solution of the linear programming model reaches the global minimum. The digital verification and application analysis proved that the algorithm is reliable, accurate, and applicable to computer-aided in situ cylindricity measurement of industrial context.